Factors determining Islamic financial literacy among undergraduates / Mohamad Azmi Abdullah, Siti Nur Aqilah Ab Wahab, Salehudin Sabar, Falah Abu - Abdullah, Mohamad Azmi; Sabar, Salehudin; Abu, Falah (Faculty of Business and Management, Universiti Teknologi MARA, SElangor, Puncak Alam Campus, 2017)
This article is written to provide a deliberation reviews on the current context of Islamic financial literacy among students. A research was conducted through case studies carried out among the students of University Malaysia Sabah Campus W.P. Labuan and Institut Pendidikan Guru (IPG), Kampus Batu Lintang, Sarawak, a teacher training institute. The respondents are candidates to become teachers upon completing their studies. Being knowledgeable and having skill in financial literacy, especially with respect to Islamic financial products, would be a great asset to them. Based on current scenario, financial literacy in Islamic financial products should be enhanced, especially to the academicians. The findings from this research is expected to be able to determine the factors influencing Islamic financial literacy among the students. This study employs a quantitative method using questionnaires distribution for analysis puposes. Data are collected through a survey using a closed ended questionnaire. Overall, the objective of this study is to determine the determinant factors towards Islamic financial literacy among students. The implications and recommendations are provided.